Communication between PLC different vendors using OPC server improved with application device - Ignatius Deradjad Pranowo; Y. B. Theo Bagastama; Thomas A. F. Wibisono (Universitas Ahmad Dahlan, 2020)
Many industries often use different devices and controllers in automation systems. They all face the same difficulty how to exchange data between all those components. This paper proposed the implementation of OPC Server as software interface on communication between two different controllers, PLC Mitsubishi and PLC Omron. The main advantage of the method is the compatibility and solution for the factory difficulty problem because of using several driver controller. The compatibility among the different platforms of both controller, PLC Mitsubishi and PLC Omron, can be reached by use of KEPServerEx6 (OPC server) as a software interface. To test the compatibility amongst two different controllers, there was developed and implemented two field application devices, bottle unscramble and bottle filling station. This implementation shows OPC Server technology resolving data compatibility issues between different platforms and reducing development costs. It is envisaged that the method can be very useful to realize integration.